Rapid qPCR-Based Water Quality Monitoring in New York State Recreational Waters - Fernández-Baca, Cristina P.; Spirito, Catherine M.; Bae, Justin S.; Szegletes, Zsofia M.; Barott, Nathan; Sausele, Desiree J.; Brooks, Yolanda M.; Weller, Daniel L.; Richardson, Ruth E. (Frontiers in Water, 2021)
Public swimming beaches often rely on culture-based methods to determine if fecal indicator bacteria (FIB) levels are greater than health risk-based beach action values (BAV). The slow turnaround time of culture-based assays can prevent effective beach closure and reopening decisions. Faster on-site testing methods are needed. Additionally, beach closures are currently based on high FIB levels, but at-present there are no tools to examine the health risks to bathers from myriad pathogens (e.g., bacteria, viruses, protozoa) that may be present in recreational waters. Twelve New York State beaches (n=9 freshwater and n=3 marine) were monitored over the course of summer 2018, and two of the freshwater beaches were monitored in fall 2017 as part of a preliminary study. A rapid, in-field workflow for detecting fecal enterococci in water samples was tested using four assays on two Biomeme handheld devices. All Biomeme-based workflows involved in-field DNA extractions and qPCR using portable devices. Beach water samples were also analyzed using EPA-approved or EPA-based qPCR methods: two culture-based methods, Enterolert (targeting enterococci at freshwater and marine beaches) and Colilert (targeting E. coli at freshwater beaches); and one qPCR method based on EPA 1611.1. For low abundance pathogen quantification, nanoscale-qPCR was conducted in 2018 using the Pathogen Panel which targeted 12 viral, bacterial, and protozoal pathogens. In fall 2017, the qPCR-based methods performed similarly to Enterolert (r2 from 0.537 to 0.687) and correctly classified 62.5-75.0% of water samples for a BAV of 104 MPN per 100 ml. In summer 2018, the correlation between Enterococcus levels based on Biomeme qPCR and Enterolert varied substantially between the 12 beaches. Inclusion of diverse regions and beach types may have confounded the Biomeme qPCR results. The EPA 1611.1-based method showed a weak, significant correlation (r2 = 0.317, p = 0.00012) with Enterolert. Nanoscale-qPCR showed low-levels of pathogens present at all beach sites; but only 3 showed up with any substantial frequency, E. coli eae (25% of samples), norovirus (31.4%), and Giardia lamblia (11.4%). Preliminary studies to establish beach-specific correlation curves between rapid qPCR and Enterolert methods are needed before any qPCR assay is used to inform beach decisions.